Investigação da adequabilidade da cromatografia de íons para a determinação de espécies de halogênios em saliva - Mendes, Ana Luiza Garcia (2019)
In this work, ion chromatography was investigated for halogens speciation analysis in human saliva. Initially, it was used an isocratic ion chromatography system (“IC 1 System”), being evaluated: the chromatographic column (Metrosep A Supp 7 or Metrosep A Supp 5), the composition of the mobile phase (Na2CO3 or Na2CO3 + NaHCO3), the mobile phase flow rate (between 0.4 to 0.8 mL min-1, depending on the column), the temperature of the column compartment (30 to 45 °C), and the use of mobile phase modifiers (acetone). A system that allows operating in gradient mode (“IC 2 System”) was also evaluated, being optimized: the temperature of the column compartment (20 to 45 °C), the eluent flow rate (0.15 to 0.40 mL min-1) and different gradient programs (1 to 60 mmol L-1 KOH). Microwave-assisted alkaline dissolution was used to obtain the total halogen concentration by inductively coupled plasma mass spectrometry (ICP-MS). The best condition found for the “IC 1 System” was obtained with the Metrosep A Supp 7 column at 45 °C using Na2CO3 (3.6 mmol L-1) as the mobile phase, at 0.8 mL min-1. However, this condition did not provide the separation of fluoride and iodate and also, bromide, chlorate and perchlorate. The “IC 2 System” enabled the separation of bromide from chlorate and perchlorate according to the gradient elution program. The optimized conditions for the “IC 2 System” were 1 to 60 mmol L-1 KOH gradient, 0.3 mL min-1 mobile phase flow rate and column compartment temperature at 35 °C. In addition to chromatographic evaluations, the stability of halogens in saliva was also studied, as well as the use of different filtration membranes for sample pretreatment. The stability study demonstrated the viability of storage for up to 90 days under refrigeration (4 °C), without leading to losses in total Cl, Br and I concentration. Regarding the use of a filtration step as pretreatment, different membrane types were investigated and no influence was observed for Cl and Br. However, Cl contamination was observed in some filters and underestimated results were observed for iodine. Additionally, the IC systems presented wide linear range (5-10000 μg L-1), as well as low limits of detection and quantification for the investigated species. With the developed method, it was possible to identify chloride and bromide, as well as sulfate and phosphate in human saliva.